Control by state space and frequency response in a damped transfemoral prosthesis - Sotelo Valer, Freedy (2020)
ABSTRACT The present work is an applied research, that approaches the modeling and simulation of the control system by the frequency response method and the state space method in a transfemoral prosthesis with damping in the knee for applications in disabled patients. The research presents an alternative to improve the degree of independence for a person with an approximate height of 1.70m ± 2cm and a weight of 70kg ± 2kg.